TWO NEW VARIETIES OF BEGONIA HOOVERIANA FROM SULAWESI - ALVITASARI, DEVI; CHIKMAWATI, TATIK; Dorly, DORLY; RUGAYAH, RUGAYAH; ARDI, WISNU HANDOYO (Research Center for Biology, 2024)
Two new varieties of Begonia hooveriana Wiriad. from Sulawesi are described here, namely Begonia hooveriana var. rubescens Alvitasari and Begonia hooveriana var. sepangensis Alvitasari. They are distinguished based on several morphological characters: base, shape, and size of male flower tepals; peduncle length of female inflorescence; peduncle length, shape, and apex of fruits. A description of two new varieties, identification keys and its distributions are provided here.